Social Intelligence of Pupil Teachers in Relation to Their Values - Kaur, Randeep; Manral, Bheema (Far Western Journal of Education, 2024)
Social intelligence and values play a vital role in shaping and building character of any person. Being social and caring for other’s feelings are basic and fundamental characteristic of human beings. Social intelligence and values are closely and deeply related constructs. Social intelligence develops good and moral values in human beings. If at early stage of human life social intelligence is properly developed; it will later enhance high moral values in life which will benefit society. Present study is based on social intelligence of pupil teachers in relation to their values. Pupil teachers join teaching profession after completing their B.Ed. course. They will be directly responsible for developing and providing proper social situations to students learning in their schools. At the same time, it’s also up to them to develop good and moral values in the students. Therefore, the present study is very important from this perspective. The present study aims to investigate the correlation between social intelligence and values of pupil teachers. Descriptive survey method was employed in the study. A sample of 412 pupil teachers is included in the study; who were studying in B.Ed. colleges affiliated to Kumaun University Nainital. Social Intelligence scale by N.K. Chadha & Usha Ganesan and Personal Value questionnaire by G.P. Sherry & R.P. Verma were employed in the study for data collection. It is obtained from the study that social intelligence and all the values are positively correlated with each other.